Modelling and simulation of ultrasonic descaling in heat exchanger. (3rd November 2021) - Liu, Guorong
Heat exchanger is widely used in petrochemical industry, long cycle operation will lead to the generation of scaling and the reduction of heat transfer coefficient, but the traditional scale removal method is not convenient to operate with high cost. In this paper, a kind of ultrasonic descaling technology is designed, and the propagation model of ultrasonic wave in heat exchanger is established by using B-P neural network, including the propagation model of ultrasonic load on tube plate and the propagation model of ultrasonic load in medium. Based on the influence of two different ultrasonic loading modes, the propagation mechanism of ultrasonic load on the tube plate of heat exchanger was obtained by simulation research. Finally, the propagation mechanism model of ultrasonic wave in heat exchanger is established successfully through experimental verification.